Enhanced Biodegradation Of Dispersed Crude Oil Using Marine Microorganisms - Zahed, Mohammad Ali (2010)
Cleanup of oceanic oil spills continues to be an important biotechnological challenge due to the highly variable nature of spills and the large number of complicating factors introduced by the environment in which they occur. Although much research in bioremediation has been conducted in the past two decades, appropriate crude oil and nutrient concentration for application of bioremediation in the marine environment is still inconclusive. Therefore this study aims to investigate the effects of crude oil concentration on its biodegradation in seawater as well as optimization of nutrient concentration for improved hydrocarbon removal in high and low initial crude oil concentrations. In the first part of study, the effects of initial oil concentration and dispersant on the rate of bioremediation of petroleum hydrocarbons in seawater samples were investigated for four concentrations i.e. 100, 500, 1000 and 2000 mg/L. In crude oil experiments, bioreactors were supplemented with microorganisms and nutrients. KNO3 and K2HPO4 were used as nitrogen and phosphorus sources respectively. A total of 1.00 mL microorganism inocula (containing 1.2 × 107 cell /mL) were added to each bioreactor. In dispersed crude oil (DCO) experiments, bioreactors were supplemented with the dispersant Corexit 9500 at a ratio of 20:1 (w/w), crude oil-to-dispersant. In low crude oil concentrations, natural attenuation (no nutrient addition) removed 22% of crude oil in 28 days. The highest removal of 68% was observed in un-optimized condition by using nitrogen 20 mg/L and phosphorus 2 mg/L in 28 days; while process optimization exhibited a crude oil removal of 69% with nitrogen 16.05 mg/L and phosphorus 1.34 mg/L in 27 days. Thus, optimization process can improve biodegradation rate and reduce nutrient consumption.